PREPARATION OF POLYMERIC ALUMINIUM FERRIC CHLORIDE FROM BAUXITE TAILINGS - zhang, Mei; Ma, Dongyang; Guo, Min (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Bauxite tailings are the main solid wastes in the ore dressing process. The Al2O3 and Fe2O3 contents in bauxite tailings can reach 50% and 13% respectively. The present study proposed a feasible method to use bauxite tailings to prepare polymeric aluminium ferric chloride (PAFC), a new composite inorganic polymer for water purification. Bauxite tailings roasted reacting with hydrochloric acid under air, pickle liquor which mainly contains Fe3+, Al3+ was generated, then calcium aluminate was used to adjust pH value and the basicity of the pickle liquor, the PAFC was subsequently prepared after the polymerization process. The optimal synthesizing parameters for the preparation of PAFC obtained were as follows: the concentration of hydrochloric acid of 24 wt%, ratio of hydrochloric acid to bauxite tailings of 6:1, temperature of 90℃, leaching time of 2.5 hours, ration of pickle liquor to calcium aluminate of 12:1, polymerization temperature of 90℃ and polymerization time of about 3 hours. The basicity of PAFC was higher than 68%, the sum concentration of Al2O3 and Fe2O3 was beyond 12.5%. The results of flocculation tests indicate that the PAFC has a better performance of removing the turbidity of wastewater compared to PAC, and PAFC prepared by bauxite tailings is a kind of high quality flocculants.